2009
DOI: 10.1097/sap.0b013e31817f023e
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Cervical Trachea Using a Prefabricated Corticoperiosteal Flap From the Femur

Abstract: We treated a severe cervical fistula with a defect of tracheal cartilage using prefabrication of a corticoperiosteal flap combined with a cutaneous flap.The patient was a 16-year-old male with a cervical tracheal fistula that developed after a tracheostomy. Almost all the circumference of the trachea just below the cricoid cartilage up to the 4th tracheal cartilage had been lost.The reconstruction was performed in 2 series of operations as follows; repair of tracheal framework using a prefabricated corticoperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Including a vascularized bone chip introduces a new approach to total or partial closure of tracheocutaneous fistulas after tracheostomy or tumor surgery. While many authors address the multilayered structure of the defect [13], only one report on free vascularized bone transfer was found [8]. The concept of a regional myo-osteous flap of the neck was described by the myo-osteous sternocleidohyoideous flap for mandibular reconstruction in a review article by Kierner et al [9].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Including a vascularized bone chip introduces a new approach to total or partial closure of tracheocutaneous fistulas after tracheostomy or tumor surgery. While many authors address the multilayered structure of the defect [13], only one report on free vascularized bone transfer was found [8]. The concept of a regional myo-osteous flap of the neck was described by the myo-osteous sternocleidohyoideous flap for mandibular reconstruction in a review article by Kierner et al [9].…”
Section: Discussionmentioning
confidence: 98%
“…Also, the final aesthetic result is of great importance because of the visibility of the suprasternal notch. Several procedures have been advocated for closure, including multilayered advancement flaps [7,13], sternocleidomastoid muscle flaps [9], free cartilage transfer [17,2], and free flap surgery [8,3].…”
Section: Introductionmentioning
confidence: 99%
“…4,12,41,42 Our group demonstrated that this flap is also useful in the reconstruction of a perforated trachea, which has been shown in a recently published case. 43 Aside from many advantages of the medial femur condyle flap, including its low donor-site morbidity, the use of this technique is limited. The limitation is, in part, attributable to the wide anatomical variation of the descending genicular artery, which has been observed in anatomical studies focusing on the medial descending genicular artery.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, prefabricated free flaps have been investigated by different authors. [21][22][23][24][25] Although neovascularization is a natural and indispensable part of wound healing and can be selectively combined with vascular implantation and microsurgical techniques to create customized neovascularized free flaps, 26 flap prefabrication techniques still need further investigation as a result of the fact that the precise mechanisms of neovascularization are not well understood yet. 27 The survival of prefabricated flaps mostly depends on the status of angiogenesis in the prefabricated flaps through vascular induction.…”
Section: Discussionmentioning
confidence: 99%